Supply, installation, testing and commissioning of fire doors with all necessary accessories etc. for 13 storied Brac University new campus building at holding No. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Energyshield Engineering Ltd. to supply, installation, testing and commission of Fire Doors with all necessary accessories etc. for 13 storied Brac University New Campus project